Assessment of English Oral Reading Fluency Rates for Grade seven English Second Language Learners in Tanzania - Sadiki Moshi Feruzi (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
This study aimed at assessing reading rates for learners in grade seven English second language (ESL) in Morogoro region, Tanzania. A total of 220 participants were randomly selected and assigned two grade appropriate English texts to read so as determine their reading rates. Fluency scale test was used to assess pupils’ reading fluency rates and the data was statistically analysed using SPSS software. It was necessary to asses pupils’ reading rates in the study context because there are no established fluency rate norms set for grade seven pupils in the country. In this case the current study serves as a reference for improvement. Results show that grade seven pupils in Morogoro region had an average reading fluency rate of 101words per minute (WPM) for fiction text and 95WPM for non-fiction text. The difference in the two texts can be due to the length of words and difficulty level in non-fiction text against fiction text. The scored rate is below the adopted benchmarks which implies that these pupils are at risk in reading fluency, consequently, calling for immediate interventions.